2004
DOI: 10.1364/opex.12.001972
|View full text |Cite
|
Sign up to set email alerts
|

Polarization mode dispersion reduction in spun large mode area silica holey fibres

Abstract: Abstract:We report the fabrication of the first spun holey optical fibre. Our experiments show that the complex air/glass transverse structure can be retained when the preform is spun during the fibre drawing process. Measurements of differential group delay (DGD) confirm that significant reductions in polarization mode dispersion (PMD) can be readily achieved using this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…The periodicity of the twist required depends on the wavelength of light and the details of the fiber profile. Fiber preforms are normally rotated at the furnace inlet and held with zero rotation at the outlet, leaving the fiber with an overall twist along its length [7]. This strategy succeeds provided the twist periodicity (spin pitch) does not exceed the beat length, typically in the range 0.1 mm-10 cm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The periodicity of the twist required depends on the wavelength of light and the details of the fiber profile. Fiber preforms are normally rotated at the furnace inlet and held with zero rotation at the outlet, leaving the fiber with an overall twist along its length [7]. This strategy succeeds provided the twist periodicity (spin pitch) does not exceed the beat length, typically in the range 0.1 mm-10 cm.…”
Section: Introductionmentioning
confidence: 99%
“…Preservation of the microstructure has recently been demonstrated when rotating large mode-area fibers with a high density of small, dispersed holes, at rates sufficient to dramatically reduce PMD [7]. However, as discussed in [9], rotation can sometimes affect fiber geometry, thus suggesting the possibility of using preform rotation as an additional control parameter in the drawing process.…”
Section: Introductionmentioning
confidence: 99%
“…It is not obvious that the same process may be applied to holey-fibre preforms without producing adverse macroscopic geometry-changes that severely compromise the microstructure within. Preservation of the microstructure has recently been demonstrated when rotating large mode-area fibres with a high density of small, dispersed holes, at rates sufficient to dramatically improve PMD [7].…”
Section: Introductionmentioning
confidence: 99%
“…The periodicity of the twist required depends on the wavelength of light and the details of the fibre profile. Fibre preforms can be rotated as they enter the furnace and held with zero rotation at its exit, leaving the fibre with an overall twist along its length [7]. This stratagem succeeds provided the twist periodicity (spin pitch) does not exceed the beat length.…”
Section: Introductionmentioning
confidence: 99%
“…Holey fiber technology has now reached the point that km-lengths of polymer-coated HF with losses as low as 0.28dB/km at 1.55µm [10] and tensile strengths comparable to those of conventional fiber are now possible. It is also important to note that it has been shown that advanced fiber drawing techniques such as fiber spinning previously developed to reduce the Polarisation Mode Dispersion (PMD) of conventional fibers are applicable to HF fibers without compromise to the fiber structure [11].…”
Section: Fiber Fabricationmentioning
confidence: 99%